The difference between modern modes of biathlon training at the Olympic Winter Games - Wang, D. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction The biathlon is a snow sport that combines cross-country skiing and shooting, originating in Scandinavia. It requires athletes to not only have the ability to glide quickly over long distances but also to have the ability to shoot quickly and accurately. There is little research on biathlon characteristics and analysis of influencing factors and training strategies in China. Objective This study analyzes modern biathlon athletes` specific explosive power, endurance and training effects at the Winter Olympics. Methods Twenty biathlon athletes were selected as research volunteers. Physiological and biochemical indicators of the athletes were experimentally tested after training. Results There was a correlation between maximum speed and the height of the athletes` double stand test (SD) (p < 0.05). The heavier athletes skied relatively faster. However, the excessive body fat rate is not conducive to maintaining high-intensity skiing in the long term. The athletes` VO2max was closely related to their skiing performance and shot hit percentage (p < 0.05). Conclusion Maintaining gun ski training can positively improve the competitive level of world-class biathletes. The athlete's muscles have a solid ability to generate high mechanical power in a short time. It is beneficial to take advantage of a favorable position after the start of the competition.